Assessing Telemedicine Implementation Potential in High‐Referral Specialties: A Cross‐Sectional Study in Iran - Reyhane Izadi; Abdosaleh Jafari; Zahra Zare; Mohammad Amin Bahrami (Health Science Reports, 2026)
ABSTRACT Background and Aims Telemedicine is more than just an advanced technology; it represents a fundamental transformation in the delivery of healthcare services, facilitating seamless communication between patients and specialists through innovative means that are unrestricted by geographical limitations. This study aimed to identify medical specialties with the highest referral rates and assess their readiness for telemedicine implementation within the population covered by Shiraz University of Medical Sciences. Methods The study was conducted in two stages: first, identifying medical specialties with the highest patient referral frequencies, and second, assessing the potential for telemedicine implementation in these key specialties. Specialties were selected using a referral frequency threshold defined as one standard deviation above the mean number of total referrals (mean + 1 SD). To evaluate telemedicine implementation potential, four key indicators were assessed—specialists' willingness to use telemedicine, financing, organizational capacity, and practical equipment—through surveys of experts with relevant knowledge and experience in the field. A composite index was then calculated to rank the specialties, and a sensitivity analysis using alternative weighting schemes was performed to examine the stability of the rankings. Results The analysis revealed that a total of 21,328 patient referrals were recorded within the studied population during the year under review, with 70.8% (15,099) of these referrals pertaining to six key medical specialties. An assessment of telemedicine implementation potential across the six specialties showed that general surgery demonstrated the highest score (1.55), followed by cardiology (1.47), general internal medicine (1.40), orthopedics (1.38), neurosurgery (1.36), and pediatrics (1.06), representing a descending gradient from the most to the least favorable status. Conclusion The assessment of telemedicine implementation potential in key medical specialties has identified the most suitable fields for the expansion of this technology. By analyzing the critical factors influencing telemedicine adoption, this study provides actionable insights for policymakers to design targeted implementation strategies, such as sustainable financing models, enhancement of technological infrastructure, supportive regulatory frameworks, and removal of specialty‐specific barriers. These recommendations can guide the advancement of remote healthcare services in high‐demand specialties.